(untitled) (Latakia University Journal -Basic Sciences Series, 2013)
إن الهدف من البحث المقدم في هذا العمل هو إيجاد طريقة موحدة لحل مسائل الاهتزازات الطولانية في الأوساط المرنة اللزجة اللاخطية بوجود العامل البيولوجي. وحل هذه المسألة بالنسبة لقضيب منتهي الطول. The main goal of the presented research in this paper is to find a unified way to solve longitudinal vibration problems in nonlinear viscoelastic media with a biological factor. and solve the problem in a bar of finite length.